Effects of the minimum wage on employment of young adults with cognitive disabilities - Barry R. Chiswick; Hope Corman; Dhaval Dave; Nancy E. Reichman (Rockwool Foundation Berlin (RFBerlin), 2025)
This study analyzes, for the first time, the effect of increases in the minimum wage on the labor market outcomes of working age adults with cognitive disabilities, a vulnerable and low-skilled sector of the actual and potential labor pool. Using data from the American Community Survey (2008-2023), we estimated effects of the minimum wage on employment, labor force participation, weeks worked, and hours worked among working age individuals with cognitive disabilities using a generalized difference-in-differences research design. We found that a higher effective minimum wage leads to reduced employment and labor force participation among individuals with cognitive disabilities but has no significant effect on labor supply at the intensive margin for this group. Adverse impacts were particularly pronounced for those with lower educational attainment. In contrast, we found no significant labor market effects of an increase in the minimum wage for individuals with physical disabilities or in the non-disabled population.
Keywords: J14; J2; 330; Minimum Wage; Cognitive Disability; Employment; Labor Market Outcomes; American Community Survey